Kashruth -- Problems and solutions. - Schwartz, Gedalia Don (Judaism)
Discusses a variety of questions and problems dealing with kashruth laws. Policy of trust; Purification and purging of vessels; Meat related problems; Torah observance of the laws of kashruth.